Cysteine dioxygenase knockout and taurine deficiency impair mouse uterine adenogenesis by inhibiting epithelial cell proliferation and enhancing apoptosis. - Hui Liu; Yuneng Gong; Xiaoyan Qu; Sheng Cui; Di Zhang (PLoS ONE)
Uterine glands and their secretions are essential for conceptus survival and development, with abnormalities in uterine gland morphogenesis (adenogenesis) are closely related to high rates of peri-implantation embryonic loss in humans and livestock. While uterine adenogenesis occurs postnatally in most mammals, the key regulatory factors and mechanisms governing this developmental event remains largely unexplored. Our recent study reveals that cysteine dioxygenase (CDO) is highly expressed in the uterus of adult mice, which is also rich in taurine. Notably, Cdo knockout (KO) and the resulting taurine deficiency lead to the defects in embryo implantation and subfertility. However, the regulatory roles of CDO and taurine in uterine development and adenogenesis remain unclear. In the current study, we assayed CDO expression and taurine content in the developmental uteri of mice from postnatal day (PND) 3 to PND 28, and investigated the regulatory roles of CDO and taurine in uterine adenogenesis using Cdo KO mice. Our results showed that uterine CDO protein expression gradually increased from PND 3 to prepuberty, closely correlating with uterine taurine levels. Cdo KO and taurine deficiency impaired the formation and development of uterine gland by inhibiting uterine epithelial cell proliferation and enhancing cell apoptosis. Remarkably, taurine supplementation partially rescued these defects in uterine adenogenesis. These findings, for the first time, demonstrate that uterine tissue acquires the ability to synthesis taurine postnatally, CDO and taurine act as novel factors regulating uterine gland development. Uncovering the mechanisms of uterine adenogenesis could significantly improve pregnancy outcomes in humans and other mammals.